Treatment planning of intracranial lesions with VHEE: comparing conventional and FLASH irradiation potential with state-of-the-art photon and proton radiotherapy - Muscato, A.; Arsini, L.; Battistoni, G.; Campana, L.; Carlotti, D.; De Felice, F.; De Gregorio, A.; De Simoni, M.; Di Felice, C.; Dong, Y.; Franciosini, G.; Marafini, M.; et al. (Frontiers in Physics, 2023)
The treatment of deep-seated tumours with electrons of very high energies (VHEE, 70–150 MeV) has already been explored in the past, suggesting that a dosimetric coverage comparable with state-of-the-art proton (PT) or photon radiotherapy (RT) could be achieved with a large (> 10) number of fields and high electron energy. The technical and economical challenges posed by the deployment of such beams in treatment centres, together with the expected small therapeutic gain, prevented the development of such technique. This scenario could radically change in the light of recent developments that occurred in the compact, high-gradient, electron acceleration technology and, additionally, of the experimental evidence of the sparing of organs at risk achieved in ultra-high dose rate irradiation, also referred to as FLASH. Electrons with the energy required to treat intracranial lesions could be provided, at dose rates compatible with what is needed to trigger the FLASH effect, by accelerators that are a few metres long, and the organ sparing could be exploited to significantly simplify the irradiation geometry, decreasing the number of fields needed to treat a patient. In this paper, the case of two patients affected by a chordoma and a meningioma, respectively, treated with protons in Trento (IT) is presented. The proton plans have been compared with VHEE plans and X-ray intensity-modulated radiotherapy (IMRT) plans. The VHEE plans were first evaluated in terms of physical dose distribution and then assuming that the FLASH regimen can be achieved. VHEE beams demonstrated their potential in obtaining plans that have comparable tumour coverage and organs at risk sparing when benchmarked against current state-of-the-art IMRT and PT. These results were obtained with a number of explored fields that was in the range between 3 and 7, consistent with what is routinely performed in IMRT and PT conventional irradiations. The FLASH regimen, in all cases, showed its potential in reducing damage to the organs placed nearby the target volume, allowing, particularly in the chordoma case where the irradiation geometry is more challenging, a better tumour coverage with respect to the conventional treatments.